Approaches to demonstrating the effectiveness of filovirus vaccines: Lessons from Ebola and COVID-19 - Gruber, Marion F.; Rubin, Steven; Krause, Philip R. (Frontiers in Immunology, 2023)
Zaire ebolavirus (EBOV), Sudan ebolavirus (SUDV) and Marburg virus (MARV), are members of the Filoviridae family that can cause severe disease and death in humans and animals. The reemergence of Ebola, Sudan and Marburg virus disease highlight the need for continued availability of safe and effectives vaccines as well as development of new vaccines. While randomized controlled trials using disease endpoints provide the most robust assessment of vaccine effectiveness, challenges to this approach include the unpredictable size, location, occurrence and duration of filovirus disease outbreaks. Thus, other approaches to demonstrating vaccine effectiveness have been considered. These approaches are discussed using examples of preventive vaccines against other infectious diseases. In addition, this article proposes a clinical immunobridging strategy using licensed EBOV vaccines as comparators for demonstrating the effectiveness of filovirus vaccine candidates that are based on the same licensed vaccine platform technology.